2018
DOI: 10.1007/s10151-018-1770-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of primary anal sphincter repair after obstetric injury and evaluation of a novel three-choice assessment

Abstract: BackgroundThe aim of the present study was to evaluate the subjective outcome of primary repair of obstetric anal sphincter injury (OASIS) at 6 months, the factors associated with the symptoms of anal incontinence (AI), and the role of a simple survey consisting in one question with three answer choices, combined with the Wexner incontinence score for the assessment of this patient population.MethodsA retrospective cohort study was conducted on patients with third- or fourth-degree OASIS operated on between Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
1
14
0
5
Order By: Relevance
“…Our study showed a greater improvement of anal continence, with a median preoperative St. Mark’s score of 13, and a median score at long-term follow-up of 6.5. Johnson et al had a longer follow-up time, which could explain the difference, as anal incontinence is known to deteriorate with time after sphincteroplasty [18, 19, 23, 2729]. On the other hand, it is important to note that separate suturing of the internal and the external anal sphincters was not performed in the patients in the above-mentioned study, and this could also explain why our study showed a better outcome.…”
Section: Discussionmentioning
confidence: 65%
“…Our study showed a greater improvement of anal continence, with a median preoperative St. Mark’s score of 13, and a median score at long-term follow-up of 6.5. Johnson et al had a longer follow-up time, which could explain the difference, as anal incontinence is known to deteriorate with time after sphincteroplasty [18, 19, 23, 2729]. On the other hand, it is important to note that separate suturing of the internal and the external anal sphincters was not performed in the patients in the above-mentioned study, and this could also explain why our study showed a better outcome.…”
Section: Discussionmentioning
confidence: 65%
“…A study which surveyed consultant members of both the Association of Coloproctology of Great Britain and Ireland and the RCOG, reported that only 10% of colorectal surgeons had a high level of experience (described as >4 repairs per year) in repairing OASIs, compared to 46.5% of the O&G cohort ( P < 0.001) 15 . A Finnish centre found that all grade four tears were repaired by O&Gs 16 . Experience is important for both detecting and repairing tears 17 .…”
Section: Discussionmentioning
confidence: 99%
“…En la revisión de la Cochrane de 2013 (8) no se hallan diferencias estadísticamente significativas entre ambas técnicas en relación con el dolor perineal, la dispareunia, incontienencia para aires ni incontinencia fecal, sin embargo si se observa una reducción estadísticamente significativa de la Urgencia defecatoria en la esfinteroplastia. Por otra parte, el estudio de Kuismanen et al (9) en el que comparan ambas técnicas no encuentran diferencias estadísticamente significativas, aunque indican que los desgarros más leves se repararon con esfinterorrafia y los más graves con esfinteroplastia. Por desgracia, la mayor parte de los estudios son series cortas y retrospectivas, en las que la experiencia personal del cirujano y la escuela marcan la manera de hacerlo, siendo muy difícil de demostrar la superioridad de una u otra técnica.…”
Section: Figura 5 Imagen De La Esfinteriplasia a Los 6 Meses Discusiónunclassified